Development of complaint management system for Pejabat Pengurusan Fasiliti UiTM Shah Alam / Noor Hisham Affizam Shamsuddin - Shamsuddin, Noor Hisham Affizam (2006)
Information technology is changing dramatically, largely due to the forces unleashed by major advances in computing, networking, and storage technology. Web sites and webbased system computerization is the most popular medium that is used by organizations to promote their product and services. Currently, the process of forwarding complaint towards the organization by using the ADKRS pin 3/98 form or by phone call to direct line customer service known as helpdesk. The complaint later will be key in into the existing conventional system which hundred percent depend on the complaint report. This required a lot of time key in many complaints by users. This thesis discusses a web-based development for Pejabat Pengurusan Fasiliti Universiti Teknologi MARA, Shah Alam called Complaint Management System or e-Complaint. The system is very useful to the user because it will change manual conventional method to system computerized. Therefore, the objectives of the project are to identify the current process of forwarding complaint, procedure involved in managing the complaint and to determine the problems faced within the organization. The system would help the users and administration to access and monitor complaint easily via Internet. The project will produce new system